The effect of whole body vibration on gait stability in individuals with Parkinson's disease: a preliminary study. (2nd January 2023) - Silveira-Ciola, Aline Prieto; Barbieri, Fabio Augusto; Soares, Carolina Favarin; Marques, Nise Ribeiro; Simieli, Lucas; Faganello-Navega, Flávia Roberta
Abstract : Background/Aims: Whole body vibration could benefit functional mobility in people with Parkinson's disease. A preliminary study was undertaken to analyse the acute effect of whole body vibration on unobstructed walking and obstacle circumvention in people with Parkinson's disease. Methods: People with Parkinson's disease and typically healthy individuals as matched controls were divided into four groups with nine individuals in each: experimental or placebo for people with Parkinson's disease and experimental or placebo for the control group. The participants were evaluated in two different gait conditions: unobstructed walking and obstacle circumvention. Then the participants undertook a session of whole body vibration on a KIKOS P201 lateral vibratory platform in two positions: feet shoulder-width apart, and feet shoulder-width apart with slightly flexed knees. The participants were re-evaluated after this session. Results: After whole body vibration, those in the experimental Parkinson's disease group had a reduced co-contraction of the tibialis anterior and the gastrocnemius lateralis muscles during unobstructed walking, whereas the co-contraction of the tibialis anterior and the gastrocnemius lateralis muscles increased in the experimental control group. In addition, those in the experimental control group had reduced stride duration in unobstructed walking and in obstacle circumvention. After the placebo intervention, the co-contraction of the tibialis anterior and the gastrocnemius lateralis muscles increased in all conditions and stride duration was reduced in unobstructed walking. Conclusions: Although whole body vibration had no acute efficiency on gait (unobstructed walking and obstacle circumvention), it can improve other components, such as strength, which could be important for people with Parkinson's disease.